Linguistic Ethnography of The Nagajuang & Batang Natal - Parapat, Lili Herawati; Sitorus, Wulan Sari; Siregar, Fadia Agustina (Universitas Islam Negeri Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2024)
Between 15 September and 20 November 2024, this study conducted an ethnography of Nagajuang and Batang Natal languages. Sample of 35 first semester students from Nagajuang and Batang Natal was used as the research method of linguistic ethnography. Based on the theory that is employed, is Speaking. Ethnographic linguistic analysis results vary from region to region. One example of the results of the analysis is the setting: the word